Visual Cryptography Scheme using Novel Secret Sharing Technique - D.M.Yadav, Neha Ganvir, Sujay Deshpande (Mathematical Statistician and Engineering Applications, 2022)
Now a day there is too much traffic at the toll plazas. The vehicle has to stop on the toll plaza to pay the toll amount. Therefore, we are trying to develop a system that would pay the toll amount automatically and reduce the traffic at the toll plaza. In our system, by using image processing technology vehicle number is recognized to identify the number plate from real time reflections. Webcam is used to capture number plate of the vehicles. Templates matching technique identifies originals. The vehicle number is then matched with the accessible database of all the vehicles. System will check the database; if match is found then toll amount will be deducted from the user’s account. Notification will be sent to the user via message. By using image processing technology the system will work automatically and also will reduce the traffic at the toll plazas which indirectly results in the reduction of time.